If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 1) = 3x + -16 Reorder the terms: 5(1 + 2x) = 3x + -16 (1 * 5 + 2x * 5) = 3x + -16 (5 + 10x) = 3x + -16 Reorder the terms: 5 + 10x = -16 + 3x Solving 5 + 10x = -16 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + 10x + -3x = -16 + 3x + -3x Combine like terms: 10x + -3x = 7x 5 + 7x = -16 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + 7x = -16 + 0 5 + 7x = -16 Add '-5' to each side of the equation. 5 + -5 + 7x = -16 + -5 Combine like terms: 5 + -5 = 0 0 + 7x = -16 + -5 7x = -16 + -5 Combine like terms: -16 + -5 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| X+11Y=35 | | 7x+1.5=y | | 5-(x+1)=4-(2x+3) | | -3x=-3t-12 | | 2x^2+3= | | 8-8x=93-43x | | -60-9x=-14-9x | | 13d+4=5d+52 | | 73-6x=31 | | 5(x-5)=7.2 | | 3x+9=44 | | -3=-3t-12 | | 6(a+1)=30.6 | | 2u^2-2u-1=0 | | 29.8=4c-5 | | 4e-2=28.4 | | 7p=11.9 | | 56.25=2x^2+y^2 | | 6(x-9)=0 | | p=0.1x^2 | | (x+1).3=(x-2).2 | | 2(a+9)=26 | | p=2X | | 4x+4=3x+5 | | x+4=2x-7 | | (3u^2+2u-1)-(-6u^2+2u+2)+(6u^2+9u+2)= | | 3x-1=7-4(6-2x) | | 6(t+-2)-76=142 | | -5(r-3)-2(2r+1)=-8 | | 4(2b+3)=-3(b-1)+20 | | 36+7.1=2.5b+11.5 | | 4-5x=2x+1 |